Pengembangan Bahan Ajar Ilmu Pengetahuan Alam Berbasis Model Learning Cycle 7E untuk Siswa Sekolah Dasar - Fembriani Fembriani; Muhamad Taufik Hidayat (SEJ (Science Education Journal), 2018)
The purpose of this study is to examine the validity of Natural Science teaching materials for fifth grade of elementary school. The development of this teaching material focused on "Human digestive devices, food and health'' material. The product developed was teaching material based on 7E Learning Cycle learning model (LC7E teaching material). The validity measurements were done by technique of expert validity and content validity. Teaching materials are legitimate if they reach "good" and "very good" categories. The level of validity of LC7E teaching material is on the valid criteria with an average score of 3.8 and a 95% success. The result of the content validity of the 24 questions given by the data obtained an average of r count of 0.575 > r table 0, 514. With that results, the teaching material developed is declared valid.